Genetic engineering and trade: panacea or dilemma for developing countries - Pohl Nielsen, Chantal; Robinson, Sherman; Thierfelder, Karen (International Food Policy Research Institute, 2000)
Advocates of the use of genetic engineering techniques in agriculture contend that this new biotechnology promises increased productivity, better use of natural resources and more nutritious foods. Opponents, on the other hand, are concerned about potentially adverse implications for the environment and food safety. In response to consumer reactions against genetically modified (GM) foods in some countries - particularly in Western Europe - crop production is being segregated into GM and non-GM varieties. This paper investigates how such changes in the maize and soybean sectors may affect international trade patterns, with particular attention given to different groups of developing countries.